An analysis of the counterterrorism (CT) and counterinsurgency (COIN) operations employed by African Union Mission in Somalia (AMISOM) to counter the threat of al-Shabaab in Somalia (2007- 2016) - Ndegwa, Loise W (Department of Political Studies, 2019)
More than ten years after the deployment of the first African Union Mission in Somalia (AMISOM) troops to Mogadishu, it is imperative that an in-depth analysis is conducted to examine whether the troops have reduced the threat of al-Shabaab in Somalia and the region. This analysis is especially important since AMSIOM is the latest attempt to create a stable and strong central government in Somalia since the fall of Said Barre’s regime in 1991. The extremist group, al-Shabaab, has evolved to become the strongest opponent and obstacle to the creation of the Federal Government of Somalia. The main objective of this dissertation is to challenge the definition of success advocated by AMISOM and its allies regarding their progress in Somalia. This study also aims to analyse the effectiveness of the counterterrorism (CT) and counterinsurgency (COIN) operations employed by AMISOM to reduce the threat of al-Shabaab. To analyse the effectiveness of the CT and COIN operations utilised between 2007 and 2016, this paper will contextualise the body-count approach using data collected from African Union (AU) and United Nations (UN) reports and the Global Terrorism Database (GTD) by the University of Maryland. This study concludes that the weak mandate, which prevented the troops from conducting military offensives, and inadequate troop strength during the first phase of the mission (2007-July 2010), provided al-Shabaab with the right environment to evolve from a terrorist group into an insurgency by securing their support both their domestic and international support. Also, AMISOM’s failure to change their tactics and strategy to account for modifications adapted by al-Shabaab during the second and third phases (July 2010 – May 2012 and June 2012 – December 2016) has contributed to their limited success in Somalia. Although the scope of this study does not discuss all possible reasons for the limited success by AMISOM, it contributes to the larger discussion.